Surgical Resection of Post-Traumatic Heterotopic Calcification in an Athlete: A Case Report - Luciano, Alexandre Paiva; Iniesta, Luís Gustavo (Brazilian Journal of Case Reports, 2026)
Heterotopic calcification due to muscular trauma, also known as myositis ossificans, is a recognized complication in athletes, although it is not uncommon. One of the first steps in reducing sports-related injuries is to better understand the nature and extent of this pathology. Here, we present a case report of the surgical resection of heterotopic ossification in the adductor muscle of a soccer athlete, including a description of the surgical technique used for resection in the adductor muscle. We describe a 28-year-old male patient, a former professional soccer player who continues to maintain a high level of athletic activity. He reported that after a strain of the right thigh adductor muscle, he developed persistent pain and functional limitation of the hip joint. Clinical investigation and complementary examinations were initiated, leading to the diagnosis of heterotopic ossification in the right adductor muscle. After diagnostic confirmation and eight months of unsuccessful conservative treatment, with persistent limitation and decreased athletic performance, surgical resection of the osseous fragment was proposed.